A semi-automated microfluidic platform for real-time tracking of cancer cells and investigation of nanoparticles cellular uptake - Carvalho, M. R. (2017)
Statement of Purpose: Circulating tumor cells (CTCs) have been highly studied due to its implication in cancer dissemination and metastases. Thus, an approach capable of hindering their dissemination could help prevent 90% of cancer deaths (1). Labeled nanoparticles (NPs) have been proposed to track cells and monitor the efficiency of any new cancer therapy in real time. The association of NPs to a microfluidic device, such as Vena8 biochips (Figure 2), allows the accomplishment of functions in vitro that are not easily imaginable in conventional biological analysis (e.g., simulation of physiological flow and shear stress). This novel approach may expedite therapies’ validation and its successful translation into clinics. In this study, we aim to develop an improved platform composed of labeled dendrimer nanoparticles and a microfluidic device for realtime monitoring of cancer cells fate